“My Words, My Copyright”: Justifiability of Performer Owning ‘Speech’ or ‘Address’ (Journal of Intellectual Property Rights (JIPR), 2023)
The Indian Copyright Act, 1957 provides for exclusive rights to the creator of an intellectual piece, defined as workunder the Act, by granting certain rights for commercial exploitation of the same, for a limited period. The basic reading ofjurisprudence of copyright gives us two primary findings (required for the present research), i.e., there is a differencebetween a work, and its author, and a performance, and its performer; and that the author may or may not be the owner ofthe work. This further enunciates that the rights vested in the work and the performance is different from each other.This understanding finds an exception in terms of the provisions laid down under the proviso Clause (cc) of Section 17,which in effect talks about who shall be the first owner of a particular work. The preliminary understanding of theprovisions suggests that in the case of the speech or addresses, the performer will also become the ‘first owner’ of the workitself and will enjoy the rights of Section 14 for literary work as well as the performance. There is no dispute that the authorof the work will be the person who creates the work, but the ownership is deemed to be of the person delivering the speechor address, or of such other person who delivers it on behalf of someone else.The present research aimsto understand the rationale behind the promulgation of such a provision through amendment,which was passed with an objective to meet international obligations, with a discussion on its relevance in present times, andtries to justify the existence of the situation, by specifically mentioning out the scenarios which can and cannot seek theprotection of this provision.